Perception and Attitude of Undergraduates toward Online Learning Platforms in Post-Covid-19 - Abdulmumin, Ismail Abiodun; Makinde, Semiu Olawale; Sulyman, Bola Mariam (Bumi Publikasi Nusantara, 2025)
This study examined the perception and attitude of undergraduates toward online learning platforms (OLPs) in the post-COVID-19 era in Kwara State, Nigeria. The COVID-19 pandemic forced educational institutions to adopt virtual learning environments, making it essential to understand students' experiences because these insights are critical for improving education delivery in the new normal. A descriptive survey design was employed, and data were collected from 383 undergraduates across federal, state, and private universities selected through random sampling. A structured questionnaire measured three variables: perceived usefulness, perceived ease of use, and overall attitude toward OLPs. The findings revealed that students generally held positive perceptions and attitudes, although variations were observed based on gender and institution type because of differences in access, digital literacy, and learning environments. This study underscores the importance of inclusive digital strategies and infrastructure to support equitable and effective learning experiences across Nigeria’s higher education system.